Sex-based prognostic implications of nonobstructive coronary artery disease: results from the international multicenter CONFIRM study - Leipsic, Jonathon; Taylor, Carolyn M.; Gransar, Heidi; Shaw, Leslee J.; Ahmadi, Amir; Thompson, Angus; Humphries, Karin; Berman, Daniel S.; Hausleiter, Joerg; Achenbach, Stephan; Al-Mallah, Mouaz; Budoff, Matthew J.; et al. (Radiology, 2014)
To determine the clinical outcomes of women and men with nonobstructive coronary artery disease ( CAD coronary artery disease ) with coronary computed tomographic (CT) angiography data in patients who were similar in terms of CAD coronary artery disease risk factors, angina typicality, and CAD coronary artery disease extent and distribution.Institutional review board approval was obtained for all participating sites, with either informed consent or waiver of informed consent. In a prospective international multicenter cohort study of 27 125 patients undergoing coronary CT angiography at 12 centers, 18 158 patients with no CAD coronary artery disease or nonobstructive (<50% stenosis) CAD coronary artery disease were examined. Men and women were propensity matched for age, CAD coronary artery disease risk factors, angina typicality, and CAD coronary artery disease extent and distribution, which resulted in a final cohort of 11 462 subjects. Nonobstructive CAD coronary artery disease presence and extent were related to incident major adverse cardiovascular events ( MACE major adverse cardiovascular events ), which were inclusive of death and myocardial infarction and were estimated by using multivariable Cox proportional hazards models.At a mean follow-up ± standard deviation of 2.3 years ± 1.1, MACE major adverse cardiovascular events occurred in 164 patients (0.6% annual event rate). After matching, women and men experienced identical annualized rates of myocardial infarction (0.2% vs 0.2%, P = .72), death (0.5% vs 0.5%, P = .98), and MACE major adverse cardiovascular events (0.6% vs 0.6%, P = .94). In multivariable analysis, nonobstructive CAD coronary artery disease was associated with similarly increased MACE major adverse cardiovascular events for both women (hazard ratio: 1.96 [95% confidence interval CI confidence interval : 1.17, 3.28], P = .01) and men (hazard ratio: 1.77 [95% CI confidence interval : 1.07, 2.93], P = .03).When matched for age, CAD coronary artery disease risk factors, angina typicality, and nonobstructive CAD coronary artery disease extent, women and men experience comparable rates of incident mortality and myocardial infarction.
EVALuna2:12015